2007
DOI: 10.1063/1.2450650
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced formation of Zn nanocrystal islands in a SiO2 layer

Abstract: Electron-beam-induced Zn nanocrystal islands were formed in a dielectric SiO2 layer. When a ZnO thin film on a p-type Si with amorphous SiOx interface layer is subjected to a 900°C annealing followed by electron irradiation in a transmission electron microscope environment, an amorphous Zn2xSi1−xO2 layer is formed. Upon irradiation with a 300keV electrons, metallic and single crystal nanoislands of Zn with ∼7–10nm diameter were formed and embedded within the SiO2 interface layer. Possible mechanisms for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…the e-beam is the sole (or largely main) agent triggering and driving the synthesis process. This criterion excludes well-established techniques performed inside TEMs such as: electron-beam induced deposition (EBID) [1][2][3][4] and thermally assisted beam induced crystallization 5,6 since they require significant hardware add-ons (gas supplies, flow-cells and holders with heating stages) to assist the action of the e-beam in order to proceed successfully. The "in situ" requirement also filters out techniques such as electron-beam lithography 7,8 since they are not "in situ compatible".…”
Section: Introductionmentioning
confidence: 99%
“…the e-beam is the sole (or largely main) agent triggering and driving the synthesis process. This criterion excludes well-established techniques performed inside TEMs such as: electron-beam induced deposition (EBID) [1][2][3][4] and thermally assisted beam induced crystallization 5,6 since they require significant hardware add-ons (gas supplies, flow-cells and holders with heating stages) to assist the action of the e-beam in order to proceed successfully. The "in situ" requirement also filters out techniques such as electron-beam lithography 7,8 since they are not "in situ compatible".…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 10,11 reported the precipitation of crystalline zinc nanoparticles about 7 nm in diameter in zinc-rich borosilicate glass under high intensity electron irradiation. Formation of metallic zinc nanocrystals about 7-10 nm in size embedded in an amorphous silica layer by electron beam irradiation of a zinc oxide thin film on silicon substrate has been reported by Kim et al 12 . Amorphous zinc nanoparticles were initially formed under thermal annealing followed by prolonged irradiation.…”
Section: Introductionmentioning
confidence: 78%
“…The EDS spectrum demonstrated that the formed layer at the ZnO/Si heterointerface region consisted of Zn, Si, and O atoms, indicative of the formation of the Zn 2x Si 1−x O 2 layer. The formation of the amorphous Zn 2x Si 1−x O 2 layer was attributed to an interdiffusion of Zn, O, and Si atoms existing in the heterointerface region due to thermal treatment, resulting in the concomitant increase in the thickness of the amorphous interface layer [25,26]. The crystalline ZnO nanocrystals with sizes of 5-8 nm were embedded in the amorphous oxide layer, as determined from the HRTEM images shown in Fig.…”
Section: Methodsmentioning
confidence: 96%